Mantle Cell Lymphoma and Involvement of the Orbit and Ocular Adnexa - Elham Vali Khojeini; Benjamin H. Durham; Mingyi Chen (Hindawi Limited, 2013)
Orbital and ocular adnexal lymphomas are rare and represent around 1-2% of lymphomas and about 8% of the extranodal lymphomas. However, these entities represent the majority of orbital malignancies. Lymphomas of the ocular adnexal region are primary or secondary lymphomas, and the majority of them are composed of small, mature lymphocytes, which provide a large differential diagnosis. Thus, these entities are not easily distinguished from indolent lymphoid processes such as reactive lymphoid hyperplasia. Extranodal marginal zone lymphoma is the most common lymphoma in the ocular adnexal region. However, this entity cannot be distinguished from benign lymphoid proliferations or other lymphomas composed of small, mature lymphocytes by routine histopathology. We describe a 78-year-old man who presents with bilateral upper eyelid masses, which had been present and grew in size over the past twelve months prior to his presentation. A biopsy of the mass shows a monotonous population of small, mature lymphocytes. The immunohistochemical studies performed on the eyelid mass confirmed a monoclonal proliferation of B cells expressing cyclin-D1; therefore, a final diagnosis of mantle cell lymphoma was rendered. A literature review of mantle cell lymphoma with orbital and ocular adnexal involvement and the diagnostic pitfalls in this area of hematopathology are discussed.